(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article scientifically studies the technology of canned fruit production using namata fruits. The biologically active substances contained in namata fruits, including vitamins, antioxidants and minerals, were analyzed and their beneficial effects on human health were highlighted. During the study, the processing technologies of namata fruits were studied in detail, in particular, the stages of washing, cleaning, drying and canning. Optimal technological conditions for improving product quality and ensuring long-term storage during the production process were discussed, including temperature regime, sterilization methods and the use of natural preservatives. Based on the results obtained, recommendations were given on preserving the nutritional value of namata canned fruits and delivering quality products to consumers. The economic efficiency and market demand of the product were also analyzed, and the possibilities of its application in the food industry were considered.